1991
DOI: 10.1073/pnas.88.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of binocular deprivation on the development of clustered horizontal connections in cat striate cortex.

Abstract: Intrinsic horizontal axon collaterals in the striate cortex of adult cats specifically link columns having the same preferred orientation; consequently, retrograde tracer injections result in intrinsic labeling that is sharply clustered. We have previously shown that the normal development of this circuitry involves the emergence of crude clusters from an unclustered pattern during the second postnatal week. Crude clusters are later refined to the adult level of specificity by the selective rearrangement of ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(94 citation statements)
references
References 19 publications
(39 reference statements)
2
91
1
Order By: Relevance
“…We found large-scale pruning of the branches of these axons over the course of vocal learning, unlike axon arbors that have been described in other developing systems (Crepel et al, 1976(Crepel et al, , 1980Lichtman, 1977;Smolen and Raisman, 1979;Changeux, 1980, 1981;Johnson and Purves, 1981;Shatz, 1984, 1986;Rubin, 1985;Young and Rubel, 1986;Callaway and Katz, 1991;Agmon et al, 1993;Antonini and Stryker, 1993;Catalano et al, 1996;Gan and Lichtman, 1998). Additionally, the dramatic changes in overall volume of the DLM terminal field within lMAN could be explained by changes in spatial extent and degree of overlap between individual DLM axon arbors.…”
Section: Abstract: Axons; Songbirds; Vocal Learning; Topographic; Recontrasting
confidence: 43%
See 1 more Smart Citation
“…We found large-scale pruning of the branches of these axons over the course of vocal learning, unlike axon arbors that have been described in other developing systems (Crepel et al, 1976(Crepel et al, , 1980Lichtman, 1977;Smolen and Raisman, 1979;Changeux, 1980, 1981;Johnson and Purves, 1981;Shatz, 1984, 1986;Rubin, 1985;Young and Rubel, 1986;Callaway and Katz, 1991;Agmon et al, 1993;Antonini and Stryker, 1993;Catalano et al, 1996;Gan and Lichtman, 1998). Additionally, the dramatic changes in overall volume of the DLM terminal field within lMAN could be explained by changes in spatial extent and degree of overlap between individual DLM axon arbors.…”
Section: Abstract: Axons; Songbirds; Vocal Learning; Topographic; Recontrasting
confidence: 43%
“…For example, adult patterns of connec- tivity within developing sensory systems emerge as a result of extensive elaboration of axonal branches within restricted regions of postsynaptic targets. This increase in the number of axonal branches is accompanied by the elimination of a relatively small number of branches within "inappropriate" areas Shatz, 1984, 1986;Young and Rubel, 1986;Callaway and Katz, 1991;Agmon et al, 1993;Antonini and Stryker, 1993;Catalano et al, 1996;Snider et al, 1999). Thus, nascent axon arbors tend to be simple in shape and restricted in extent, and initial axonal connections can be extremely specific (Crowley and Katz, 1999).…”
Section: Axon Arbor Regression: Pruning As An Atypical Feature Of Remmentioning
confidence: 99%
“…In congenital blindness, normal sensory experience is absent during development, and, as a result, brain areas that mainly subserve visual functions in sighted individuals undergo dramatic plastic changes in blind individuals. The visual cortex of blind individuals is smaller in terms of surface area and volume (Noppeney et al, 2005;Bridge et al, 2009;Park et al, 2009), but is increased in thickness (Bridge et al, 2009;Jiang et al, 2009;Park et al, 2009), which is consistent with disturbances in synaptic pruning and the elimination of exuberant neonatal connectivity that would normally establish the specificity of visual cortical organization based on sensory experience (Singer and Tretter, 1976;Movshon and Van Sluyters, 1981;Huttenlocher et al, 1982;Callaway and Katz, 1991). Strikingly, a wealth of studies has consistently demonstrated an altered functional role for occipital areas of blind individuals.…”
Section: Introductionmentioning
confidence: 82%
“…1976; Movshon and Van Sluyters, 1981;Huttenlocher et al, 1982;Callaway and Katz, 1991;Katz and Shatz, 1996). Indeed, a distinguishing feature of neuronal activity in visual cortex is the spread of fast-traveling waves along horizontal connections (Sato et al, 2012), which may underlie integration of information across large areas of cortex.…”
Section: Discussionmentioning
confidence: 99%
“…These connections spread evenly across large regions of the cortex shortly after birth, gradually coalesce, and eventually form the clustered patterns seen in the adult (Callaway and Katz, 1990). In accord with the need for correlated visual input to drive the final development of long-range connections, it has been shown that binocular deprivation leads to poor segregation of these developing connections (Callaway and Katz, 1991). In the model, as orientation tuning gets initiated due to prenatal amplification and smoothing of initial random biases in geniculocortical connections, activitydependent processes could lead to initial clustering of long-range connections, and correlations present in the visual environment could subsequently produce long-range correlations in the map of complex cells, which could in turn drive associative learning of the adult pattern of long-range connections (Callaway and Katz, 1990).…”
Section: Discussionmentioning
confidence: 98%